الضوابط الشرعية للمهنة في الضوء السنة النبوية المطهرة - Mohd Sobali, A.; Nazri, A.; Sakat, A.; Abdul Majid, L. (Universiti Sains Islam Malaysia, 2024)
Everybody in this world could not imagine living without a career. It is because work or career is needed by every single human to support, fulfill his or her desire and to provide the complete life. In order to achieve these purpose, people choose several types of profession such as trading, agriculture, services, administrations and many more. In order to generate productivity, for sure we will look at the European people and Japanese spirit of working. We are wondering at their working behavior, spirits, discipline and diligence. They are in front of us for too many steps. Physically, human design and body shape in this world are same. But the problem is the disciplines of working among them are so different than ours. So what is the reason which causes we are too slow in this aspect? And what is the Islamic principle of career brought to us by al-Quran and al-Sunnah? Based on al-Quran and prophetic tradition perspectives, and views of Muslims great scholars, this research is focusing on the prophetic principles of career which are very important matter to be highlighted among Muslims in order to improve the quality of working discipline, motivate the workers and uphold their spirit of diligence.